2021
DOI: 10.3390/vaccines9080933
|View full text |Cite
|
Sign up to set email alerts
|

The Credibility of Health Information Sources as Predictors of Attitudes toward Vaccination—The Results from a Longitudinal Study in Poland

Abstract: Background: The research focused on the relationships between attitudes towards vaccination and the trust placed in different sources of information (science, experts and the information available on the Internet) before and during COVID-19. Method: A longitudinal design was applied with the first measurement in February 2018 (N = 1039). The second measurement (N = 400) was carried out in December 2020 to test if the pandemic influenced the trust in different sources of information. Results: The final analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Results from a study conducted in Slovenia demonstrated the positive association between confidence in official sources (experts, public health institutions) and the intention to get vaccinated [ 52 ]. According to a study in Poland, the amount of confidence in physicians and science was linked to similar changes in views regarding vaccination [ 68 ].…”
Section: Confidence In the Healthcare System Government And Public He...mentioning
confidence: 99%
“…Results from a study conducted in Slovenia demonstrated the positive association between confidence in official sources (experts, public health institutions) and the intention to get vaccinated [ 52 ]. According to a study in Poland, the amount of confidence in physicians and science was linked to similar changes in views regarding vaccination [ 68 ].…”
Section: Confidence In the Healthcare System Government And Public He...mentioning
confidence: 99%
“…Organized anti-vaccine movements spreading their arguments through websites, which are growing in popularity, are also an important source of information for vaccine skeptics. People who refuse vaccination justify their position most frequently by their fear of the side effects of vaccination, their belief that vaccinations do not in fact protect against disease, and their distrust of pharmaceutical companies [11][12][13][14].…”
Section: What Drives Vaccine Skepticism?mentioning
confidence: 99%
“…A large proportion of the respondents, however, did not have a positive opinion about the vaccination program as a source of information, and this may be of great importance when it comes to understanding the attitude of the general population. The limited accuracy of the information on the internet is often a result of the fact that anyone can potentially publish health information [ 44 ]. Moreover, internet sources are often blamed for the rise in vaccine skepticism because of their role in spreading misinformation on an unprecedented scale, which is used by anti-vaccination movements.…”
Section: Discussionmentioning
confidence: 99%